2012
DOI: 10.1186/1471-2350-13-81
|View full text |Cite
|
Sign up to set email alerts
|

MC1R variants predisposing to concomitant primary cutaneous melanoma in a monozygotic twin pair

Abstract: BackgroundConcomitant primary cutaneous melanoma in monozygotic twins has been reported in only two pairs but in neither of them genetic analysis was performed. Two high-penetrance susceptibility genes, CDKN2A and CDK4 and one low-penetrance gene, MC1R, are well-defined genetic risk factors for melanoma. MITF has been recently identified as a novel intermediate risk melanoma-predisposing gene.Case presentationWe describe the extraordinary occurrence of a primary cutaneous invasive melanoma in two 44-year-old i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
6
0
2
Order By: Relevance
“…A germline homozygous MC1R R151C variant was detected in a woman with skin type I, red hair and ‘white’ dysplastic nevi who developed two amelanotic melanomas . We recently reported the occurrence of concomitant primary hypomelanotic melanoma on the same body site in a pair of red‐haired monozygotic twins, heterozygous for two MC1R R variants . In the present series, four patients presented a hypo/amelanotic melanoma and all carried at least one R variant in the MC1R genotype two being homozygous for R variants (R151C/R160W and R142H/R151C), one heterozygous R / r (R151C/V60L) and one R /wt (R160W/wt).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…A germline homozygous MC1R R151C variant was detected in a woman with skin type I, red hair and ‘white’ dysplastic nevi who developed two amelanotic melanomas . We recently reported the occurrence of concomitant primary hypomelanotic melanoma on the same body site in a pair of red‐haired monozygotic twins, heterozygous for two MC1R R variants . In the present series, four patients presented a hypo/amelanotic melanoma and all carried at least one R variant in the MC1R genotype two being homozygous for R variants (R151C/R160W and R142H/R151C), one heterozygous R / r (R151C/V60L) and one R /wt (R160W/wt).…”
Section: Discussionmentioning
confidence: 55%
“…The association of MC1R RHC variants and melanomas lacking significant pigmentation has been described in two case reports . A germline homozygous MC1R R151C variant was detected in a woman with skin type I, red hair and ‘white’ dysplastic nevi who developed two amelanotic melanomas .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Outros estudos também identificaram diversas variantes do MC1R relacionadas com susceptibilidade ao melanoma (Ghiorzo et al, 2012;Pellegrini et al, 2012). A compreensão da expressão e regulação deste receptor é essencial para que se compreenda seus efeitos sobre a melanogênese e o risco de melanoma (Swope et al, 2012 …”
Section: Bancos De Dados De Genomas Completosunclassified
“…Other studies have also identified several MC1R coding variants related to melanoma susceptibility (Ghiorzo et al, 2012;Pellegrini et al, 2012). Understanding the expression and activity regulation of this receptor is essential to comprehend its effects on melanogenesis and melanoma risk (Swope et al, 2012).…”
Section: A Introductionmentioning
confidence: 99%